2008
DOI: 10.1111/j.1600-0579.2007.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the preclinical prosthodontic training at the Faculty of Dentistry, University of Bergen, Norway

Abstract: The curriculum of the dental faculty at the University of Bergen was revised and a new curriculum was implemented in 2000. The first candidates graduated in 2003. In the new curriculum the theoretical teaching consists of an extended integrated lecture series in prosthodontics and biomaterials. The revised laboratory course includes an increased number of tooth preparations performed on phantom heads solely. Newer types of preparations based on bonding technique, such as ceramic crowns, veneers and inlays, hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Mack (21) observed that a minimal taper of 12 degrees was necessary to ensure the absence of undercuts. The widely recommended 12°TOC has been Copyright shown to be difficult to achieve for many dental students (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Mack (21) observed that a minimal taper of 12 degrees was necessary to ensure the absence of undercuts. The widely recommended 12°TOC has been Copyright shown to be difficult to achieve for many dental students (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Dental students should be able to formulate a diagnosis or a management plan based on an integrated interdisciplinary approach, which is a core of a successful dental treatment. For all the reasons mentioned in this article, further attempts should be made to improve preclinical courses, to increase the competence of dental students and in consequence the skills of future dental personnel, which will positively influence the quality of the treatment offered to the patients (Ingebrigtsen et al, ).…”
Section: Oral Biology Dental Technology and Dental Sciences; An Examentioning
confidence: 99%
“…To accommodate for these rapid changes that are and will continue to affect all segments of the healthcare professions many attempts were made to improve preclinical dental courses. This is to increase the competence of students and consequently increase the skill of future practitioners and thus of the quality of the treatment offered to patients (Ingebrigtsen et al, ). Examples include, gene therapy, which is predicted to be a part of a new opportunity for dental personnel to expand their treatment options (Baum and O'Connell, ).…”
Section: Oral Biology Dental Technology and Dental Sciences; An Examentioning
confidence: 99%
“…Very little information is available concerning the ability of dentists in Africa to prepare teeth for full cast restorations [8]. There are many studies which followed the performance of dental students in tooth preparation for fixed prosthodontics during their pre-clinical course [23,24] and efforts for accurate evaluation of their preclinical work were done [25,26].…”
Section: Introductionmentioning
confidence: 99%